PROBLEM BASED LEARNING CONCEPTS OF BIOLOGY TO IMPROVE OUTCOMES AND ATTITUDES CARING THE ENVIRONMENT - Arpina; Haryono, Agus; Nomeritae; Edy Gunawan, Yohanes; Abudarin; Ludang, Yetrie (Acta Scientiae et Intellectus, 2024)
Education is the main thing to prepare the next generation who are ready to compete in the 21st century. Now, improving the quality of education is needed to face competition in the era of globalization. The learning device is a form of preparation made by the teacher before carrying out the learning process. Teaching preparation is one measure of a teacher’s success. Failure in planning is tantamount to planning failure. This implies how important it is to prepare learning through the development of learning tools. The lesson plan is a plan that describes the procedures and organization of learning to achieve a basic competency that has been defined in content standards and described in the syllabus. Learning outcomes can be interpreted as the maximum results that have been achieved by students after experiencing the teaching and learning process in learning certain subject matter. Learning outcomes are not absolutely in the form of values, but can be in the form of changes or improvements in attitudes, habits, knowledge, persistence, fortitude, reasoning, discipline, skills and so on that lead to positive change. Therefore, the curriculum is designed to be able to develop the potential of students into abilities that are increasing in attitudes, knowledge and skills.